Design of a 5G Fixed Wireless Access (FWA) Network at 3.5 GHz Frequency in Urban Areas: A Case Study of Kambang Iwak Park, Palembang: Perancangan Jaringan 5G Fixed Wireless Access (FWA) pada Frekuensi 3.5 GHz di Area Urban: Studi Kasus Taman Kambang Iwak Palembang - Sari, Melia; Prasetio, Robi; Dalimunthe, Abdul Haris; Saputra, Iwan Pahendra (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2025)
The provision of fiber optic infrastructure in dense urban areas like Taman Kambang Iwak, Palembang, often faces constraints related to excavation permits and potential damage to city aesthetics. 5G-based Fixed Wireless Access (FWA) technology serves as a strategic alternative solution to deliver high-speed broadband access without requiring physical cable installation to the user's premises. This study aims to design a 5G FWA network utilizing the 3500 MHz frequency (Band n78) with a 100 MHz bandwidth. The design was conducted through simulation using RadioPlanner 3.0 software with the Okumura-Hatta propagation model tailored for urban environmental characteristics. Analyzed parameters included signal coverage based on Reference Signal Received Power (RSRP), Reference Signal Received Quality (RSRQ) and data capacity (throughput). Simulation results indicate that the design scenario using three sectoral antennas is capable of providing "Good" category signal coverage in the target area. In terms of data performance, the system achieves a maximum downlink throughput of up to 750 Mbps and uplink ranging from 500 Mbps to 750 Mbps. (Discussion) Based on these results, the implementation of 5G FWA at the 3.5 GHz frequency is proven feasible and meets the standards for high-speed data service requirements in the Taman Kambang Iwak area..